A (4‐fluorophenyl)(phenyl)phosphine oxide‐modified epoxy resin with improved flame‐retardancy, hydrophobicity, and dielectric properties. Issue 31 (2nd April 2021) - Duan, Haodong; Xu, Xiaolei; Leng, Kangwei; Zhang, Sheng; Han, Yuxi; Gao, Jun; Yu, Qing; Wang, Zhongwei
Abstract: The compound (4‐fluorophenyl)(phenyl) phosphine oxide (4‐FPO) was designed, synthesized, and used in the modification of epoxy resin (EP). The 4‐FPO‐modified EP was prepared by curing the reaction mixture of diglycidyl ether of bisphenol A (DGEBA) and 4‐FPO in the presence of 4, 4′‐diaminodiphenylsulfone (DDS). Compared with the unmodified EP, the limiting oxygen index value of the EP/4‐FPO‐0.6 (4‐FPO‐modified EP with 0.6 wt% of phosphorus) increased to 31.6%, and the sample achieved UL‐94 V‐0 rating. The peak of the heat release rate, average of the heat release rate, and total heat release of EP/4‐FPO‐0.6 were reduced by 39, 24, and 19%, respectively. Mechanism study showed that the quenching effect in the gas and barrier effect in the condensed phase were responsible for the enhanced flame‐retardant properties of the 4‐FPO‐modified EP. The results showed that hydrophobicity and dielectric properties of the modified EP were clearly improved. Abstract :